Long-Term Outcome After Adoptive Immunotherapy With Natural Killer Cells: Alloreactive NK Cell Dose Still Matters - Parisi, Sarah; Ruggeri, Loredana; Dan, Elisa; Rizzi, Simonetta; Sinigaglia, Barbara; Ocadlikova, Darina; Bontadini, Andrea; Giudice, Valeria; Urbani, Elena; Ciardelli, Sara; Sartor, Chiara; Cristiano, Gianluca; et al. (Frontiers in Immunology, 2022)
Recently, many reports were published supporting the clinical use of adoptively transferred natural killer (NK) cells as a therapeutic tool against cancer, including acute myeloid leukemia (AML). Our group demonstrated promising clinical response using adoptive immunotherapy with donor-derived alloreactive KIR-ligand-mismatched NK cells in AML patients. Moreover, the antileukemic effect was correlated with the dose of infused alloreactive NK cells (“functional NK cell dose”). Herein, we update the results of our previous study on a cohort of adult AML patients (median age at enrollment 64) in first morphological complete remission (CR), not eligible for allogeneic stem cell transplantation. After an extended median follow-up of 55.5 months, 8/16 evaluable patients (50%) are still off-therapy and alive disease-free. Overall survival (OS) and disease-free survival (DFS) are related with the dose of infused alloreactive NK cells (≥2 × 105/kg).